Dielectric and impedance properties of Nd3/2Bi3/2Fe5O12 ceramics - Jawahar, K.; Behera, Banarji [UNESP]; Choudhary, R. N. P. (Springer, 2009)
The polycrystalline sample of Nd3/2Bi3/2Fe5O12 was prepared by a high- temperature solid-state reaction technique. Preliminary X-ray structural analysis exhibits the formation of a single-phase tetragonal structure at room temperature. Microstructural analysis by scanning electron microscopy shows that the sintered sample has well defined grains. These grains are distributed uniformly throughout the surface of the sample. Detailed studies of dielectric response at various frequencies and temperatures exhibit a dielectric anomaly at 400 A degrees C. The electrical properties (impedance, modulus and conductivity) of the material were studied using a complex impedance spectroscopy technique. These studies reveal a significant contribution of grain and grain boundary effects in the material. The frequency dependent plots of modulus and the impedance loss show that the conductivity relaxation is of non-Debye type. Studies of electrical conductivity with temperature demonstrate that the compound exhibits Arrhenius-type of electrical conductivity. Study of ac conductivity with frequency suggests that the material obeys Jonscher's universal power law.